Earthquake-resistant structural design through energy demand and capacity. - Surahman, Adang
An energy-based earthquake-resistant structural design method is proposed. The proposed method uses specific input energy spectra, modal or time-history analyses, and energy distribution among structural members. For a given member strength and stiffness, a relationship between the energy attributable to damage absorbed by a member and its cumulative ductility demand can be determined. Member strength, stiffness and energy capacity are design parameters which are simultaneously used in the design. The method can avoid soft-storey design. The damage is measured based on a cumulative basis considering earthquake magnitude, frequency, and duration. Tests have been carried out to determine energy absorbing capacities of various structural components. More efforts are needed to make the energy-based earthquake-resistant structural design practical, but ssimple formulations for this method are possible.
Keywords: Energy-based design; Cumulative ductility; Plastic ductility; Equivalent velocity; Energy distribution; Energy capacity